Electrical Stimulation-Guided Approach to Pulmonary Artery Catheter Ablation in Patients with Idiopathic Pulmonary Arterial Hypertension: A Pilot Feasibility Study with a 12-Month Follow-Up. (17th February 2020) - Goncharova, Natalia S.; Moiseeva, Olga M.; Condori Leandro, Heber Ivan; Zlobina, Irina S.; Berezina, Aelita V.; Malikov, Kirill N.; Tashkhanov, Dmitry M.; Lebedev, Dmitry S.; Mikhaylov, Evgeny N.
Abstract : Background . Recently, transcatheter pulmonary artery (PA) ablation aiming at sympathetic denervation has been proposed in pulmonary arterial hypertension (PAH). This pilot feasibility study aimed to assess the feasibility of selective radiofrequency PA ablation based on response to high-frequency stimulation mapping. Methods . The study comprised 3 female patients with idiopathic PAH (IPAH). The following reactions to PA stimulation were noted and marked by color points on the three-dimensional map: sinus bradycardia (heart rate decrease ≥15%), tachycardia (heart rate increase ≥15%), phrenic nerve capture, and cough. Since the most appropriate ablation strategy was unknown, two approaches were suggested, according to stimulation results: ablation at points with any heart rate response (either bradycardia or tachycardia)—this approach was applied in patient #1 (IPAH long-term responder to calcium channel blockers); segmental ablation at points with no response and with tachycardia response (one IPAH long-term responder to calcium channel blockers patient and one–IPAH with negative vasoreactive testing). Hemodynamic measurements were performed before and after denervation. Follow-up visits were scheduled at 6 and 12 months. Results . Six-months follow-up was uneventful for patients #1 and 3; patient #2 had one syncope and reduced 6-minute walk test distance and peak VO2 consumption. At 12 months, there was a normalization of mean PA pressure and pulmonary vascular resistance (PVR) in patient #1. Patient #2 had no change in PA pressure and PVR at 12 months. Patient #3 remained in II functional class; however, there was an increase in mean PA pressure and loss of vasoreactivity. Conclusions . Electrical high-frequency stimulation of the PA identifies several types of evoked reactions: heart rate slowing, acceleration, phrenic nerve capture, and cough. The improvement in clinical and hemodynamic parameters following targeted PA ablation in the IPAH patient with positive vasoreactive testing should be confirmed in larger studies.